Caspase-3 can not be Used to Predict the Response to Neoadjuvant Chemotherapy Regiment PVB in Cervical Cancer Stage IB-IIA - Ambari, Ediwibowo (Indonesian Journal of Obstetrics and Gynecology, 2013)
Objectives: To determine the factors that may be used as the prognostic parameter for the therapeutic efficacy of neoadjuvant chemotherapy, which can be used to revising the management of early stage cervical cancer patients with large lesions. Methods: This was a retrospective cohort study. The study was conducted in the Dr. Cipto Mangunkusumo Hospital, Faculty of Medicine, University of Indonesia. The subjects were 15 cervical cancer stage IB2 and IIA patients with lesionsâ size of > 4 cm, who would be treated with neoadjuvant chemotherapy, consisted of cisplatin 50 mg/m2, vincristine 2 mg/m2 and bleomycin 15 mg regiment. The patientsâ response would be evaluated after completing 3 series of chemotherapy. Data was retrieved from medical records and cervical biopsy paraffin blocks and examined histopathologically using IHC staining to see expression of caspase-3 with histoscore assessment score. Data was analyzed by univariate, bivariate analysis. Results: Response to PVB neoadjuvant chemotherapy was found in 5 out of 15 patients. None of the clinicopathology variables can be used to predict response to therapy. Expression of caspase-3 as a marker of apoptosis, can not predict the response of the therapy before administrating neoadjuvant chemotherapy either. There is a significant difference between the levels of caspase-3 in epidermoid carcinoma with adenocarcinoma, with p value of 0.02 (RR 6;95% CI 1.69-21.26). Conclusion: Clinicopathologic factors and the expression of caspase-3 before getting chemotherapy neoadjuvant can not predict the succeed of the therapy. [Indones J Obstet Gynecol 2013; 1-3: 156-60] Keywords: caspase -3, clinicopathologic, early-stage cervical cancer lession in large, neoadjuvant chemotherapy response to therapy